A buffering mechanism for IP mobility support in 6LoWPAN-WSN under critical environment. (2018) - Khan, Riaz Ahmed; Mir, Ajaz Hussain
With the advent of internet of things (IoT), IP mobility has become an inexorable service to wireless sensor networks (WSN). Existing mobility support protocols suffer extra packet loss due to conventional mobility operations, hence are not applicable to critical mobile applications. Therefore, this paper proposes a packet buffering mechanism (PBM) to reduce extra packet loss occur during Layer 2 (L2) mobility. In the mechanism, hand-off (HO) is anticipated and triggered before the actual movement of the mobile node (MN) and domain gateway routers assisting mobility will buffer packets for the MN during L2 mobility when the MN is not able to hear from any of the access networks (ANs). The advance HO initiation leads to Layer 3 (L3) HO before L2, thus eliminating L2 channel scanning process. The evaluation of proposed PBM shows improvements against existing solutions with HO-delay of 15ms and average packet loss of 2-4%.